Whales & nations : environmental diplomacy on the high seas - Dorsey, Kurkpatrick (Weyerhaeuser environmental book., 2013)
"Before commercial whaling was outlawed in the 1980s, diplomats, scientists, bureaucrats, environmentalists, and sometimes even whalers themselves had attempted to create an international regulatory framework that would allow for a sustainable whaling industry. In Whales and Nations, Kurkpatrick Dorsey tells the story of the international negotiation, scientific research, and industrial development behind these efforts--and their ultimate failure. Whales and Nations begins in the early twentieth century, when new technology revived the fading whaling industry and made whale hunting possible on an unprecedented scale. By the 1920s, declining whale populations prompted efforts to develop 'rational'--what today would be called sustainable--whaling practices. But even though almost everyone involved with commercial whaling knew that the industry was on an unsustainable path, Dorsey argues that powerful economic, political, and scientific forces made failure nearly inevitable. Based on a deep engagement with diplomatic history, Whales and Nations provides a unique perspective on the challenges facing international conservation projects. This history has profound implications for today's pressing questions of global environmental cooperation and sustainability. Kurkpatrick Dorsey is associate professor of history at the University of New Hampshire; 'This important book is essential for understanding the formation of the first global environmental agreements. It is valuable both as an argument about the failures of sustainability and as an authoritative guide to the people and issues behind the rise of global environmental awareness in the twentieth century'--Jacob Darwin Hamblin, author of Arming Mother Nature; 'Whales and Nations offers a fresh and timely look at the intersection of the twentieth-century whaling industry, international diplomacy, and science and is an important contribution to a topic that loomed very large in the environmental movement at a critical point in its development. It's also a great read'--Helen M. Rozwadowski, University of Connecticut, Avery Point; 'The international politics of whaling underwent seismic shifts over the course of the twentieth century, reflecting complex changes in attitudes toward marine mammals and environmental protection worldwide. This important story has never been better told than in Kurkpatrick Dorsey's new book, which is likely to be the standard work on this subject for a long time to come'--William Cronon"--